Chemical etching of CdTe, CdₓHg₁-ₓTe, ZnₓCd₁-ₓTe and Te in the HNO₃-HCl-citric acid - Tomashik, Z.F.; Bilevych, Ye.O.; Feichuk, P.I.; Tomashik, V.M. (Functional Materials, 2005)
The peculiarities of CdТе, CdTe, CdₓHg₁-ₓTe, ZnₓCd₁-ₓTe and Те single crystals dissolution in the solutions of HN0₃-HCl-citric acid system are investigated and the surfaces of equal etching rates (Gibbs diagrams) are constructed. The limiting stages of dissolution process and regions of polishing solutions for these semiconductors are determined. Increasing of ZnТе contents in the Cd₁-ₓZnₓТе solid solutions has been shown to result in a linear increasing of dissolution rate. Исследованы особенности растворения CdTe, CdₓHg₁-ₓTe, ZnₓCd₁-ₓTe и Те в растворах системы HNO₃-HCl-лимонная кислота и построены поверхности одинаковых скоростей растворения (диаграммы Гиббса). Определены лимитирующие стадии процесса растворения и области растворов, которые могут использоваться для химического полирования этих полупроводников. Показано, что увеличение содержания ZnТе в составе твердых растворов Cd₁-ₓZnₓТе приводит к линейному увеличению скорости растворения. Дослiджено особливостi розчинення монокристалiв CdTe, CdₓHg₁-ₓTe, ZnₓCd₁-ₓTe та Те в розчинах системи HNO₃-HCl-лимонна кислота та побудовано поверхнi однакових швидкостей розчинення (дiаграми Гiббса). Визначено лiмiтуючi стадi'ї процесу розчинення та областi розчинiв, що можуть використовуватися для хiмiчного полiрування цих напiвпровiдникiв. Показано, що збiльшення вмiсту ZnТе у складi твердих розчинiв Cd₁-ₓZnₓТе приводить до лiнiйного збiльшення швидкостi розчинення.